Indirect Vector Controlled Asynchronous Motor Driveâ€™s Dynamic Performance and Analysis with A New Modified MPPT Controller - Pakkiraiah, B; Paul Ratnakanth, Pallam; Haribabu, Ch; Chandra Sekhar, O (International Journal of Engineering and Technology, 2018)
Generation of electricity from the PV system has nowadays chosen as a best energy collecting source, due to its abundance availability and also to save the conventional energy sources to the future generation. Because all the conventional sources are coming to an extinct. That is the reason, everybody are looking towards the available renewable energy resources like wind, solar, bio mass, ocean, tidal and geothermal. But, upon those, solar and wind sources are maximum preferred sources, due to their easy availability and easy way of collection of energy. This paper presents a modeling of solar photovoltaic (PV) array with a new modified maximum power point tracking (MPPT) controller, which enhances the PV system performance even at abnormal weather conditions. That the existed MPPT controllers were developed based upon the ideal characteristics of constant irradiance with variable temperature and constant temperature with variable irradiance. To overcome the above problem a practical data is considered for designing of MPPT controller which is based upon variable irradiance. But here, it is developed with the variable irradiance and variable temperature with better performance of the system. The output obtained from the PV with a new modified MPPT is given to the boost converter with an inverter to find the dynamic performance of an indirect vector controlled asynchronous motor drive under different operating conditions. For inverter control, a space vector modulation (SVM) algorithm is used, in which the calculation of switching times is proportional to the instantaneous values of the reference phase voltages. The dynamic performance responses like phasor current, torque and speed of the drive by the new modified MPPT along with SVM controlling technique of the inverter are compared and analyzed with the existed method for different operating conditions.Â Â